2009
DOI: 10.1080/01612840902722187
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Depression Treatment in Low-Income, Unmarried, Adolescent Mothers in a Southern, Urban Area of the United States

Abstract: This study explored barriers to depression treatment in low-income, unmarried, adolescent mothers in a southern, urban area of the United States. The authors utilized a phenomenological approach and focus group methodology. Participants (n = 9) were enrolled in a teen parent program, an option of the public school system. The metaphor of a merry-go-round emerged from the data and represented the ups and downs that the adolescent mothers experience as they struggle to adjust to the role of mother. Their knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…The low rate of treatment seeking in this study was consistent with results from an earlier study by Logsdon, Hines‐Martin, and Rakestraw (). In a focus group with nine adolescent mothers, only one participant reported that she would see a counselor, if talking with her boyfriend did not help (Logsdon et al., ).…”
Section: Postpartum Depression In Adolescent Motherssupporting
confidence: 92%
See 1 more Smart Citation
“…The low rate of treatment seeking in this study was consistent with results from an earlier study by Logsdon, Hines‐Martin, and Rakestraw (). In a focus group with nine adolescent mothers, only one participant reported that she would see a counselor, if talking with her boyfriend did not help (Logsdon et al., ).…”
Section: Postpartum Depression In Adolescent Motherssupporting
confidence: 92%
“…In a focus group with nine adolescent mothers, only one participant reported that she would see a counselor, if talking with her boyfriend did not help (Logsdon et al., ). Other participants reported that they would seek help from their support group, pray or go to church, write feelings down, play with the baby, and sleep (Logsdon et al., ).…”
Section: Postpartum Depression In Adolescent Mothersmentioning
confidence: 99%
“…The prevalence rate of a major depressive episode in the puerperium ranges from 12% to 16% (Viguera et al, 2011;Elisei et al, 2013); this prevalence rises to 26% among young unmarried mothers (Logsdon et al, 2009;Venkatesh et al, 2014). Approximately, from 5% to 20% of nursing women develop postpartum depression (PPD) within the first 6 months after delivery (O'Hara and McCabe, 2013;Wynter et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Of particular concern, by 12 months postpartum no adolescent mothers had pursued referrals for mental health evaluation and treatment (Logsdon, 2008). Barriers to mental health treatment for adolescent mothers include personal barriers (e.g., lack of knowledge of depressive symptoms and depression treatment, life challenges that interfere with attention to mental illness; Logsdon, Hines-Martin & Rakestraw, 2009) and health service barriers (e.g., provider requirement that parental permission and presence is needed before treatment; lack of insurance coverage; National Academy of Sciences, 2008; MBaye & Logsdon, 2005). The intention to seek mental health treatment in adolescent mothers has been predicted by subjective norms, such as a personal experience with mental health treatment, mother’s history of depression and depression treatment, and family facilitation of treatment (Logsdon, Usui, Pinto Foltz & Rakestraw, 2009).…”
mentioning
confidence: 99%